PENGEMBANGAN E-MODUL BERBASIS FLIP PDF CORPORATE EDITION PADA TEMA 7 SUBTEMA 1 PEMBELAJARAN 1 KELAS V SDN 39 PONTIANAK KOTA - Muhammad Ridho Hakiki; Dyoty Auliya Vilda Ghasya; Siti Halidjah (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
This research generally has the aim of producing an E-Module based on Flip PDF Corporate Edition media for 5th grade elementary school students valid and practically to be used in assisting thematic learning activities, theme 7 sub-theme 1 learning 1. The method used in this study is Brog and Gall's method. The data sources in this study were a homeroom teacher, 33 students, fifth grade of B class of SDN 39 Pontianak Kota and 2 expert validators, namely design and material experts. The results showed that the development of E-Modules based on Flip PDF Corporate Edition has passed seven stages of research, including: determining potential and problems, collecting data, making product designs, conducting design validation, revising design parts, carrying out product trials, and revising product parts. The practicality of E-Module development products based on Flip PDF Corporate Edition has a category of